Analysis of food safety issues in Ukraine exported to the European Union market in 2024 - M. R. Simonov; O. A. Pronina; B. V. Gutyj; M. M. Akymyshyn; T. О. Pundiak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Despite the significant challenges facing domestic food producers, food exports, raw materials, and feed are growing. To further increase the range of domestic food products on the trading floors of the European Union countries, market operators must prove the safety and quality of the products offered. The European Union uses one of the most developed and effective food safety control systems in the world since the health of citizens is the highest priority of the community's activities. This work aimed to analyze non-compliance with EU requirements for the safety of food products exported from Ukraine through information messages of the Rapid Alert System for Food and Feed that appeared in 2024. As the analysis showed, the main problems of domestic food safety are associated with non-compliance with microbiological criteria and improper use of agrochemicals and veterinary drugs, the residual amounts of which exceeded the maximum permissible concentrations. Individual cases concerned using prohibited and restrictedly permitted food additives in producing food products. Isolated cases of physically hazardous factors in food products were registered. A significant part of food safety problems is associated with insufficient harmonization of domestic legislation with EU legislation in consumer product safety control. Problems related to the duration of crossing the state border of Ukraine in 2024 led to several reports of non-compliance with temperature regimes during the transportation of food products. Notably, the number of complaints about food products exported from Ukraine is not higher than that of other exporting countries. The main number of complaints had low-risk categories.